Estudio de pertinencia de la oferta educativa de docentes en educación básica, en la provincia de El Oro, Ecuador - Espinoza Freire, Enrique (2018)
Exploratory and descriptive study aimed at determining the technical and social relevance of the career training of teachers in basic education, the Technical University of Machala, in Ecuador, which refers to the ability of the school to express answers coherent and comprehensive to the needs and demands of society. In this sense and for purposes of the study methodology was used as a theoretical tool: analysis and synthesis, for the literature review and the theoretical construct, plus analysis of results due to the application of empirical methods as the survey, review documentary. Also in this paper some indicators of educational quality in reference to the training of teachers, and the impact on education services by graduates and perception of educational managers on teaching skills discussed, likewise determined in Prospective student entering first year of basic education of 8,439 per year until 2017; on the other hand, it resulted in labor demand is at 4,456 places for graduates of the career of this study reason. Further evaluation of the program is revealed to measure compliance with education policies by the system and control of the quality parameters established in Ecuador, so that the program benefited students and reach the appropriate skills to perform the work stations own output profile designed and meets the challenge of forming a more qualified human resources and the training work.